2021
DOI: 10.1136/jitc-2020-001925
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional iRGD-anti-CD3 enhances antitumor potency of T cells by facilitating tumor infiltration and T-cell activation

Abstract: BackgroundPoor infiltration and limited activation of transferred T cells are fundamental factors impeding the development of adoptive cell immunotherapy in solid tumors. A tumor-penetrating peptide iRGD has been widely used to deliver drugs deep into tumor tissues. CD3-targeting bispecific antibodies represent a promising immunotherapy which recruits and activates T cells.MethodsT-cell penetration was demonstrated in tumor spheroids using confocal microscope, and in xenografted tumors by histology and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…CD3 + T cells are membrane markers of mature T lymphocytes that can be used to quantify the total number of T lymphocytes [19]. When CD3 + cells was increased, it represented a higher tumor lymphatic infiltration and a higher amount of tumor-killing immune cells, which has a protective effect on the organism [37,38]. This result supports the idea that our proposed Deep-immune score may be sufficient to predict prognosis of CRC.…”
Section: Discussionsupporting
confidence: 77%
“…CD3 + T cells are membrane markers of mature T lymphocytes that can be used to quantify the total number of T lymphocytes [19]. When CD3 + cells was increased, it represented a higher tumor lymphatic infiltration and a higher amount of tumor-killing immune cells, which has a protective effect on the organism [37,38]. This result supports the idea that our proposed Deep-immune score may be sufficient to predict prognosis of CRC.…”
Section: Discussionsupporting
confidence: 77%
“…Many studies have reported that iRGD peptide accelerates drug delivery into tumor cells ( Tian et al, 2014 ). After its combination with integrins, the enzyme hydrolysate promotes the tissue penetration of the drug ( Zuo, 2019 ; Zhou et al, 2021 ). We found that NRP-1 was highly expressed in colon cancer tissues and cell lines, enabling the iRGD-Exos to be effectively ingested by colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the CPP‐iRGD is the key to facilitating tumour penetration and T‐cell activation. In 2021, bifunctional iRGD‐anti‐CD3 was found to enhance the anti‐tumour potency of T cells by facilitating tumour infiltration and T‐cell activation 259 . Furthermore, the combination therapy with iRGD‐antiCD3 and PD‐1 blockade enhances the anti‐tumour capacity of cord blood‐derived T Cells 260 .…”
Section: Strategies For Anti‐tumour Immunotherapymentioning
confidence: 99%
“…In 2021, bifunctional iRGD-anti-CD3 was found to enhance the anti-tumour potency of T cells by facilitating tumour infiltration and T-cell activation. 259 Furthermore, the combination therapy with iRGD-antiCD3 and PD-1 blockade enhances the anti-tumour capacity of cord blood-derived T Cells. 260 The mechanism of iRGD is illustrated in Figure 6.…”
Section: Strategies For Anti-tumour Immunotherapymentioning
confidence: 99%